EXPERIMENTAL CHARACTERIZATION OF THE PERFORMANCES OF A STORAGE EXCHANGER WITH TUBE BANK AIR-PHASE CHANGE MATERIALS (Nigerian Journal of Technology, 2015)
This study aims to show the preliminary results of an improved components and characteristics of heat exchanger air and Phase Change Material (PCM)that was designed, dimensioned, manufactured and tested in the laboratory (with melting temperature ranging between 27-29° C), especially for refreshing semi-passive air in summer period. The preliminary results show that one of the exchanger’s storage of the system manages to refresh the air during about 8 - 10 hours. About 7-8 hours are needed to regenerate the PCM. The current (0.8) and the theoretical load lose (1) are appreciably the same. This system was integrated into a prototype of solar house of positive energy that has already been presented in Madrid in June 2010 during inter- university competition on Solar Decathlon in Europe (http://www.napevomo.com, www.sdeurope. org). Since there are still some issues with the ability of the containers system of the PCM to fill, drain, and dilate and conduct energy therefore further study may have to focus on the development of simulation model to overcome such weakness. http://dx.doi.org/10.4314/njt.v35i1.7